(untitled) (Journal of EAHIL, 2015)
The goal of this section is to have a look at references from non-medical librarian journals, butÂ interesting for medical librarians (for lists and TOC’s alerts from medical librarian journals, see: http://www.chu-rouen.fr/documed/eahil67.html). Acknowledgement to Informed Librarian Online